2015
DOI: 10.2147/dddt.s79383
|View full text |Cite
|
Sign up to set email alerts
|

Paracellular permeation-enhancing effect of AT1002 C-terminal amidation in nasal delivery

Abstract: BackgroundThe identification of permeation enhancers has gained interest in the development of drug delivery systems. A six-mer peptide, H-FCIGRL-OH (AT1002), is a tight junction modulator with promising permeation-enhancing activity. AT1002 enhances the transport of molecular weight markers or agents with low bioavailability with no cytotoxicity. However, AT1002 is not stable in neutral pH or after incubation under physiological conditions, which is necessary to fully uncover its permeation-enhancing effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…AT1002 also activates ΔG and the zonula occludens toxin. [24][25][26][27] Our previous study confirmed that AT1002 enhances the delivery of topically applied siRNA., and deeper dermal siRNA penetration can substantially improve its efficacy at treating skin diseases such as AD. 9,12,28) The target protein selected for AD treatment in this study was NF-κB (RelA).…”
Section: Introductionsupporting
confidence: 69%
“…AT1002 also activates ΔG and the zonula occludens toxin. [24][25][26][27] Our previous study confirmed that AT1002 enhances the delivery of topically applied siRNA., and deeper dermal siRNA penetration can substantially improve its efficacy at treating skin diseases such as AD. 9,12,28) The target protein selected for AD treatment in this study was NF-κB (RelA).…”
Section: Introductionsupporting
confidence: 69%
“…Tight junctions are cell junctions that connect neighboring cells and control the paracellular pathway of molecules. AT1002 is a hexamer synthetic peptide (H-FCIGRL-OH), which reversibly opens the tight junctions of the stratum granulosum and has biological activity similar to ΔG and zonula occludens toxin, increasing the paracellular transport of drugs across the epithelial barrier [18,19,20,21]. We have reported that the application of AT1002 can reversibly open tight junctions and increase intradermal siRNA delivery [22].…”
Section: Introductionmentioning
confidence: 99%
“…The peptide AT1002 is an analog of Vibrio cholera toxin, acting on zonula occludens in tight junctions. Peptide AT1002 enhances IN permeation by binding its receptor reversibly and opening tight junctions [ 40 ].…”
Section: Penetration Enhancers In In Drug Deliverymentioning
confidence: 99%